The Base‐Promoted Annulation of 2‐Hydrazinyl Pyridine and CO2 toward Triazolones. Issue 21 (26th September 2017) - Wu, Xiaopeng; Sun, Song; Wang, Bingbing; Cheng, Jiang
Abstract: A base‐promoted annulation of 2‐hydrazinyl pyridine and atmospheric pressure of CO2 has been developed in the presence of silane as reducing reagent, affording a series of triazolones in moderate to excellent yields. CO2 served as a carbonyl source in this transfomation. Moreover, benzamidrazones also worked well under this procedure. Thus, it represents a green, sustainable and straightforward pathway to access triazolone frameworks. Abstract :